Stress Levels And Physio-Psycho-Social Responses On Undergraduate Nursing Students Undertaking Their Thesis At Harapan Bangsa Institute Of Health Sciences, Purwokerto: A Correlation Study - Murniati, Murniati; Triana, Noor Yunida; Fitriana, Adita Silvia (Universitas STRADA Indonesia, 2018)
Background: Senior nursing students possibly experience stress due to the difficulties encountered in the process of writing a thesis. The difficulties experienced are commonly making research background, looking for the related theory and proper methods, having pressure from supervisor, feeling saturated, and many more. The stress experienced by students can also cause various responses such as physical, psychological, and social. Purpose : The aim of this study is to analyze the correlation among stress levels andphysio-psycho-social responses of nursing students undertaking thesis. Methods : This analitic cross sectional study was conducted at Harapan Bangsa Institute of Health Sciences, Purwokerto on May-July 2018. A total of 117 senior nursing students undertaking a thesis were taken by simple random sampling. Research data were collected utilizing stress questionnaire and physio-psycho-social responses. The data analysis used was univariate analysis with frequencydistribution, and bivariate analysis used was Spearman Correlation. Result : Findings of this research indicated that the senior nursing students undertaking a thesis experienced moderate level of stress (51,3%) and excellent physio-psycho-social responses (73,5%). In addition, this research showed a significant relationship between stress levels with physio-psycho-social responses (p value=0,000; r=0,508). Conclusion : The results indicated that senior students undertaking thesis can experience stress varying from mildto moderate that potentially cause physio-psycho-social responses